2012
DOI: 10.1111/j.1479-8301.2012.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre population‐based dementia prevalence survey in Japan: a preliminary report

Abstract: Community-based surveys were performed in seven rural areas in Japan to investigate the prevalence of dementia and illnesses causing dementia. A total of 5431 elderly subjects were selected based on census data from 1 October 2009. In total, 3394 participants were examined (participation rate: 62.5%), and 768 dementia cases and 529 mild cognitive impairment cases were identified. Of the illnesses causing dementia, Alzheimer's disease was the most frequent (67.4%), followed by vascular dementia (18.9%), dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 13 publications
1
69
1
2
Order By: Relevance
“…This observation is inconsistent with the notion that the prevalence of dementia is higher among women in studies conducted in Japan [28,29]. Nevertheless, a finding similar to ours, i.e., a higher prevalence of MCI in men than in women, was reported by Petersen et al [30], who hypothesized that men may experience cognitive decline earlier in life but more gradually, whereas women may transition from normal cognition directly to dementia at a later age but more abruptly.…”
Section: Environ Health Prev Medcontrasting
confidence: 68%
“…This observation is inconsistent with the notion that the prevalence of dementia is higher among women in studies conducted in Japan [28,29]. Nevertheless, a finding similar to ours, i.e., a higher prevalence of MCI in men than in women, was reported by Petersen et al [30], who hypothesized that men may experience cognitive decline earlier in life but more gradually, whereas women may transition from normal cognition directly to dementia at a later age but more abruptly.…”
Section: Environ Health Prev Medcontrasting
confidence: 68%
“…In Japanese, multicenter, population-based studies, the prevalence of dementia was not high among those aged 65e74 years (less than 10%), but was higher among those aged 75 years and older. 24 The prevalence of sarcopenia exhibited the same tendency, with the prevalence rising among those aged 75 years and older. 25,26 Thus, older adults (particularly those 75 and older) are prone to both cognitive impairment and sarcopenia.…”
Section: Discussionmentioning
confidence: 66%
“…Because age is a risk factor for developing dementia, it is estimated that by 2025 4.7 million people in Japan will suffer from dementia, which is 12.8% of the population aged 65 years or over (Ministry of Health, Labour and Welfare, 2013). Ikejima et al (2012) recently showed that the prevalence of dementia in people aged 65 or over was 22.5%, which is a higher rate than that estimated by the government. It is well recognized that caring for relatives with dementia is a difficult task for family caregivers, and can lead to stress, physical and mental health problems, and even high morbidity and mortality (Baumgarten et al, 1992;Schulz, O'Brien, Bookwala, & Fleissner, 1995).…”
Section: Introductionmentioning
confidence: 84%